The Market of Electric Energy in Bulgaria and Opportunities for Risk Management by Annual Financial Futures and Phelix Options on the European Energy Exchange – EEX - Nedev, Todor (Research Papers, 2016)
The reformation of Bulgarian electric energy market is delayed too much and it does not cover the European requirements concerning the common rules for the internal market in electric energy. Contracts for long-term purchase of electric energy provide unreasonably high benefits permanently distorting market relations and by no means one can talk about equality of individual players in the market. For the same reason ‘Bulgarian Independent Energy Exchange’ EAD, established in 2014 as part of the Bulgarian Energy Holding (BEH) is unable to meet the expectations for an organized exchange market. This makes it necessary for the Bulgarian electric energy market to join the European Energy Exchange with a cash and term market being organized after their model. Such cash market will determine a wholesale price of electric energy in accordance with the momentary demand and supply on the Bulgarian market. The term market will make futures with physical delivery available to players in the trade and afterwards – probably financial futures as well, so that each player can opt for additional protection for the occupied position. The activity of NEK EAD as a ‘public provider’ of electric energy shall be terminated because practice thus far has shown that deficits are easily accumulated and embedded disproportions by NEK it being unable to cover with own revenues and logically there follows a new proposal for higher prices to end consumers.
Keywords: Market pricing; Electric energy market; Energy prices; European energy exchange – EEX